Transferring the Purchasing Role from International to National Organizations During the Scale-Up Phase of Performance-Based Financing in Cameroon - Sieleunou, Isidore; Turcotte-Tremblay, Anne-Marie; Yumo, Habakkuk Azinyui; Kouokam, Estelle; Taptue Fotso, Jean-Claude; Magne Tamga, Denise; Ridde, Valery (Taylor and Francis, 2017)
The World Bank and the government of Cameroon launched a performance-based financing (PBF) program in Cameroon in 2011. To ensure its rapid implementation, the performance purchasing role was sub-contracted to a consultancy firm and a nongovernmental organization, both international. However, since the early stage, it was agreed upon that this role would later be transferred to a national entity. This explanatory case study aims at analyzing the process of this transfer using Dolowitz and Marsh's framework. We performed a document review and interviews with various stakeholders (n = 33) and then conducted thematic analysis of interview recordings. Sustainability, ownership, and integration of the PBF intervention into the health system emerged as the main reasons for the transfer. The different aspects of transfer from international entities to a national body consisted of (1) the decision-making power, (2) the “soft” elements (e.g., ideas, expertise), and (3) the “hard” elements (e.g., computers, vehicles). Factors facilitating the transfer included the fact that it was planned from the start and the modification of the legal status of the national organization that became responsible for strategic purchasing. Other factors hindered the transfer, such as the lack of a legal act clarifying the conditions of the transfer and the lack of post-transition support agreements. The Cameroonian experience suggests that key components of a successful transfer of PBF functions from international to national organizations may include clear guidelines, co-ownership and planning of the transition by all parties, and post-transition support to new actors.